Strategies to improve remediation and ensure food safety in metal-affected sites - Ribeiro, Paula Godinho (2021)
Anthropogenic activities such as inadequate disposal of wastewater and mining are among the most relevant for soil enrichment with heavy metals. To improve soil remediation and ensure food quality in areas affected by heavy metals, three studies were conducted. The first study evaluated how exposure to Zn and/or Cd affects the growth of andropogon grass (Andropogon gayanus Kunth) plants (originally found in metal contaminated areas from zinc mining site). Plants were cultivated for seven weeks in a nutrient solution treated with Zn (142.3–854.0 μM) or Cd (0.9–13.3 μM) separately or combined with a molar ratio of 64:1 (Zn:Cd). A control treatment was grown in a solution without Cd. At the end of the experiment, the root dry weight was not affected by the addition of the metals and Zn provided a higher shoot dry weight (up to 160%) relative to control. Andropogon grass tolerated both metals better separately than when applied together. The andropogon grass was tolerant to the doses tested, and it has the potential for recovering metal contaminated areas. The second study evaluated the potential of HydroPotash (HYP), a novel potassium-fertilizer formed from the hydrothermal alteration of K-feldspar in immobilizing heavy metals from aqueous solution. HydroPotashs at natural suspension pH removed 63.8-99.9% Zn, 20.6-40.7% Cd, and 68.4-99.7% Pb from solution. HydroPotash was also tested and compared with zeolite (commercial product) to decrease soluble and extractable (DTPA) metal contents, improve fertility, microbiological activity and promote plant growth in contaminated soils from a zincsmelting area. The experiment had a randomized design, with a factorial 3x4 (amendments x doses) scheme, using three soils/substrates with differing levels of contamination (soilhigh, soilintermediate, soillow) and control treatment (soil without amendment application). The doses tested were 15, 30, 60, and 120 Mg ha1. Products were incubated with soil moisture close to the field capacity for 90 days. Increasing HYP doses resulted in effective reduction of the soluble contents of Cd, Zn, and Pb (up to 99.9% removal), decreased Cd extractability (up to 93%), and annulled Al exchangeable content. HydroPotash increased soil pH; cation exchange capacity (CEC); nutrients available content; microbial biomass carbon and fluorescein diacetate hydrolysis. The soils were cultivated with Andropogon gayanus, Eucalyptus grandis, and Heterocondylus vitalbae in this order. All species tested started growing with HYPs application from dose 60 Mg ha-1 and 15 Mg ha-1, respectively, in Soilhigh and Soilintermediate. Plant shoot dry mass was negatively correlated with bioavailable Cd and Zn and positively with pH, CEC, and Ca content. Besides promoting plant growth, HYP reduced heavy metals (Cd, Zn) absorption by plants indicating that it has potential use as an amendment in phytostabilization programs. The third study aimed to evaluate the HYP as a soil amendment to immobilize Cd in acidic soil and reduce the accumulation of Cd in rice tissues. The experiment was carried out in a greenhouse with a Cecil sandy loam soil (3 mg Cd kg-1) under two soil water regimes: flooding (4 cm above the soil surface) or field capacity. Two hydrothermal materials (HYP-1 and HYP-2) were compared with zeolite, K-feldspar + Ca(OH)2 (the raw material used for producing HYP), Ca(OH)2, and control (without amendment). HydroPotashs, raw material, and Ca(OH)2 increased pH and reduced soluble concentration of Cd (up to 99.7%) after 30 days of soil incubation. Under the flooded regime, regardless of the materials applied, plant growth was favored. HydroPotash reduced Cd content in rice biomass and grains in both tested water regimes.